DRYING BEHAVIOR AND SOME QUALITY PARAMETERS OF POTATO FINGER CHIPS USING INFRARED RADIATION - Doymaz, I (PLAPIQUI(UNS-CONICET), 2021)
The effect of different infrared (IR) powers on drying of potato finger chips was investigated in infrared dryer. The potato finger chips dried at 38, 50, 62, 74 and 88 W infrared powers and constant slice thickness of 7 mm. Results showed that drying characteristics of potato chips were greatly influenced by infrared power. The experimental drying data were fitted to seven thin-layer drying models. The models were compared on coefficient of determination (R-2), reduced chi-square (chi(2)) and root mean square error (RMSE) values between experimental and predicted moisture ratios. The Midilli and Kucuk model was found to the best in predicting the drying kinetics of potato chips during infrared drying. The effective moisture diffusivity using the Fick's diffusion model varied from 1.82x10(-9) to 3.06x10(-9) m(2)/s. It was found that the effective moisture diffusivity increased with increasing IR power. Activation energy was estimated by a modified Arrhenius type equation as 1.35 kW/kg. The results also showed that with increasing infrared power, rehydration capacity was decreased.
Keywords: Activation energy; effective moisture diffusivity; infrared drying; mathematical modelling; potato finger chips; KINETICS; SLICES; MASS; L.; Engineering